2009 IEEE/ACS International Conference on Computer Systems and Applications 2009
DOI: 10.1109/aiccsa.2009.5069404
|View full text |Cite
|
Sign up to set email alerts
|

Impact of L1 entire locking and L2 way locking on the performance, power consumption, and predictability of multicore real-time systems

Abstract: Based on the recent design trend from giant chipvendors, multicore systems are being deployed with multilevel caches to achieve higher levels of performance. Supporting real-time applications on multicore systems becomes a great challenge as caches are power hungry and caches make the execution time predictability worse. Studies show that timing predictability can be improved using cache locking techniques. However, level-1 (L1) entire locking may not be efficient if smaller amount of instructions/data compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…However, this method is not reliable; it may produce inaccurate results. The impact of I1 (level-1 instruction cache) entire locking and CL2 (level-2 cache) partial locking on the predictability of multicore real-time systems is studied in [1]. Experimental results show that for smaller code segments (like FFT), CL2 partial locking improves predictability more than I1 entire locking does; but for large applications (like MPEG4), I1 entire locking outperforms CL2 partial locking.…”
Section: S Urveymentioning
confidence: 95%
See 2 more Smart Citations
“…However, this method is not reliable; it may produce inaccurate results. The impact of I1 (level-1 instruction cache) entire locking and CL2 (level-2 cache) partial locking on the predictability of multicore real-time systems is studied in [1]. Experimental results show that for smaller code segments (like FFT), CL2 partial locking improves predictability more than I1 entire locking does; but for large applications (like MPEG4), I1 entire locking outperforms CL2 partial locking.…”
Section: S Urveymentioning
confidence: 95%
“…Cache locking is an important mechanism that adapts caches to the needs of real-time application processing. Recent studies show that the time required to perform a memory access is predictable with static/dynamic data/instruction cache locking [1][4] [5]. It is also observed that cache locking improves predictability by removing both intra-task and intertask interferences [6] [7].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Using simulations, Asaduzzaman et al [5] showed that cache locking could potentially improve cache performance and reduce power consumption. Yang et al [21] used a dynamic programming algorithm to determine the locked contents in order to improve the data cache's power consumption and performance.…”
Section: Cache Lockingmentioning
confidence: 99%
“…For multicore processors, Suhendra et al [2] discussed the benefits of partition-based locking and compares core-and task-based partitioning. Asaduzzaman et al [3] studied L1 entire cache locking and L2 way-locking. Asaduzzaman et al [4] also used a miss table at the L2 cache level to dynamically and intelligently decide what cache blocks should and should not be locked based on the number of misses.…”
Section: Relevant Workmentioning
confidence: 99%